A Novel Hyaluronic Acid-Black Rice Anthocyanins Nanocomposite: Preparation, Characterization, and Its Xanthine Oxidase (XO)-Inhibiting Properties - Liu, Ya; Peng, Bangzhu (Frontiers in Nutrition, 2022)
To promote the normal metabolism of human uric acid, high-performance hyaluronic acid-black rice anthocyanins (HAA) nanocomposite particles were successfully prepared by a simple crosslinking method as a novel xanthine oxidase inhibitor. Its structure and properties were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transform infrared spectrometry (FT-IR), and X-ray diffraction (XRD). SEM and TEM electron microscopy showed an obvious double-layer spherical structure with a particle size of 298 nm. FT-IR and XRD analysis confirmed that black rice anthocyanins (ATC) had been successfully loaded into the hyaluronic acid (HA) structure. Nanocomposite particles (embedded form) showed higher stability in different environments than free black rice ATC (unembedded form). In addition, the preliminary study showed that the inhibition rate of the nanocomposite particles on Xanthine oxidase (XO) was increased by 40.08%. These results indicate that HAA nanocomposite particles can effectively improve black rice ATC's stability and activity, creating an ideal new material for inhibiting XO activity that has a broad application prospect.